Bibliometric Analysis of Research Trends on Acupuncture for Neck Pain Treatment Over the Past 20 Years [Letter] - Zhang F (Dove Medical Press, 2021)
Fan Zhang,1 Huachun Zhang2 1Department of Nephrology, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Nursing, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Huachun Zhang Email lhhlky@163.com View the original paper by Dr Park and colleagues